Nanobotany (Springer International Publishing, 2018)
This work synthesizes research and practical work, including various techniques and applications of botany and nanoparticles, including enzymology, pharmaceuticals, phenolics, antioxidants, metal particles, synthesis of nanoparticles by plants and microbes, and more. The text discusses the latest research as well as key sources of information condensed from other scholars across the globe, providing a comprehensive resource for scholars working in nanobotany, as well as chemists and researchers in the pharmaceutical industry.